An Open-Label, Randomized, Parallel, Phase II Trial to Evaluate the Efficacy and Safety of a Cremophor-Free Polymeric Micelle Formulation of Paclitaxel as First-Line Treatment for Ovarian Cancer: A Korean Gynecologic Oncology Group Study (KGOG-3021) - Lee, Shin-Wha; Kim, Yong-Man; Cho, Chi Heum; Kim, Young Tae; Kim, Seok Mo; Hur, Soo Young; Kim, Jae-Hoon; Kim, Byoung-Gie; Kim, Seung-Cheol; Ryu, Hee-Sug; Kang, Soon Beom (Cancer research and treatment, 2018)
Genexol-PM is a biodegradable cremophor EL-free polymeric micelle formulation of paclitaxel. Here,we compared efficacy and safety of Genexol-PM plus carboplatin versus Genexol plus carboplatin for ovarian cancer treatment. In this multicenter, randomized, phase II study, patients with International Federation of Gynecology and Obstetrics IC-IV epithelial ovarian cancer were randomly assigned (1:1) to receive Genexol-PM 260 mg/m or Genexol 175 mg/m with 5 area under the curve carboplatin every 3weeks (6 cycles). The primary endpointwas the carbohydrate antigen 125 and Response Evaluation Criteria In Solid Tumor composite overall response rate (ORR). Of 131 enrolled patients, 98 were included in intention-to-treat analysis. Mean dosages were 260.00±0.00 mg/m Genexol-PM or 174.24±3.81 mg/m Genexol. Median followup was 18.0 months (range, 6.1 to 33.8 months). ORR was 88.0% (95% confidence interval [CI], 80.4 to 95.6) with Genexol-PM, and 77.1% (95% CI, 67.1 to 87.1) with Genexol (noninferiority threshold, 16.3%). Median time to progression was 14.8 months (95% CI, 11.3 to 20.2) with Genexol-PM and 15.4 months (95% CI, 13.2 to 29.6) with Genexol (p=0.550). Overall, six patients died. Neutropenia was the most common toxicity (incidences of 86.0% vs. 77.1%, p=0.120). Peripheral neuropathy incidences were 84.0% versus 64.6% (p= 0.148). Peripheral neuropathy of ≥ grade 3 occurred in one patient receiving Genexol. All toxicities were manageable. Genexol-PM plus carboplatin as first-line treatment in patients with epithelial ovarian cancer demonstrated non-inferior efficacy and well-tolerated toxicities compared with the standard paclitaxel regimen. Further studies are warranted to optimize the dose and schedule, and to investigate long-term outcomes.